2021
DOI: 10.1021/acschemneuro.1c00600
|View full text |Cite
|
Sign up to set email alerts
|

Rhynchophylline Administration Ameliorates Amyloid-β Pathology and Inflammation in an Alzheimer’s Disease Transgenic Mouse Model

Abstract: Alzheimer's disease (AD), the most common neurodegenerative disease, has limited treatment options. As such, extensive studies have been conducted to identify novel therapeutic approaches. We previously reported that rhynchophylline (Rhy), a small molecule EphA4 inhibitor, rescues impaired hippocampal synaptic plasticity and cognitive dysfunctions in APP/PS1 mice, an AD transgenic mouse model. To assess whether Rhy can be developed as an alternative treatment for AD, it is important to examine its pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Jiang et al [61] reported that Rhy, a biological component of Uncaria rhynchophylla, protects against AβO-induced toxicity in AβO-injection model mice through activation of Nrf2. Rhy administration was also shown to be capable of penetrating the BBB and ameliorating Aβ pathology and neuroinflammation in APP/PS1 mice [62]. The protective action of Rhy against AβOs may also be mediated by the antagonism of NMDA receptors containing GluN2B subunits [63].…”
Section: Nrf2 Aβo Toxicity and Ad Pathologymentioning
confidence: 97%
“…Jiang et al [61] reported that Rhy, a biological component of Uncaria rhynchophylla, protects against AβO-induced toxicity in AβO-injection model mice through activation of Nrf2. Rhy administration was also shown to be capable of penetrating the BBB and ameliorating Aβ pathology and neuroinflammation in APP/PS1 mice [62]. The protective action of Rhy against AβOs may also be mediated by the antagonism of NMDA receptors containing GluN2B subunits [63].…”
Section: Nrf2 Aβo Toxicity and Ad Pathologymentioning
confidence: 97%
“…It has comprehensive biological effects on the nervous system and are expected to treat AD in multiple targets and multiple pathways. Rhynchophylline had BBB permeability and could regulate various molecular pathways related to amyloid metabolism and inflammation in the brain of APP/PS1 mice, which was beneficial to amyloid pathology (Fu et al, 2021; Yang et al, 2018). It was also beneficial to improve amyloid deposition, could inhibit the expression of BACE, Aβ PP and Aβ, and inhibit the spatial cognitive function damage induced by soluble Aβ (1–42) by inhibiting the excessive activation of N‐Methyl‐D‐aspartate (NMDA) receptors containing nr2b outside the synapse.…”
Section: Anti‐ad Active Ingredients In Plantsmentioning
confidence: 99%
“…These chemicals usually participate in regulating neurotransmitters, hormones, and neuroregulatory cytokines to modulate cerebral metabolism. In the treatment of AD, tanshinone IIA, ginsenoside Rd, cannabidiol, oxymatrine, cholic acid, vitamin A, puerarin, icariin, geniposide and curcumin prevent and ameliorate AD by diminishing Aβ deposition and tau protein phosphorylation ( Liu et al, 2015a ; Karch and Goate, 2015 ; Zeng J. et al, 2017 ; Tang and Taghibiglou, 2017 ; Watt and Karl, 2017 ; Yan et al, 2017 ; Yao et al, 2017 ; Chen Z. et al, 2019 ; Jin et al, 2019 ; Majid et al, 2019 ; He et al, 2020 ; Fu et al, 2021 ). Cannabidiol disrupts the Wnt/β-catenin pathway to inhibit tau protein phosphorylation ( Watt and Karl, 2017 ).…”
Section: Effects Of Nmcs On Cerebral Metabolismmentioning
confidence: 99%
“…Ginsenoside Rd, salvianolic acid B and icariin can also treat AD by increasing the expression of α-secretase and soluble amyloid precursor protein alpha (sAPPα), which are negatively related to Aβ formation, or by decreasing the expression of β-secretase, γ-secretase, BACE1, sAPPβ, and amyloid precursor protein (APP), which stimulates Aβ production ( Tang et al, 2016 ; Yan et al, 2017 ; Jin et al, 2019 ). Rhynchophylline treats AD by inhibiting erythropoietin-producing hepatocellular A4 (EphA4), which is key in synaptic loss and dysfunction and mediates Aβ ( Fu et al, 2021 ). Capsaicin and salvianolic acid B inhibit AD by inhibiting glycogen synthase kinase 3 beta (GSK-3β), leading to a decrease in inflammatory signaling molecules and preventing tau hyperphosphorylation ( Tang et al, 2016 ; Xu et al, 2017 ).…”
Section: Effects Of Nmcs On Cerebral Metabolismmentioning
confidence: 99%